Discourse traditions, text linguistics, and translation studies - Albrecht, Jörn; Kunert, Irene Dorothea (Manual of Discourse Traditions in Romance)

Felix Tacke, Sprachliche Aufmerksamkeitslenkung. Historische Syntax und Pragmatik romanischer Zeigeaktkonstruktionen, Frankfurt am Main (Vittorio Klostermann) 2022, xiii + 616 p. (Analecta Romanica 92) - Kunert, Irene Dorothea (Vox Romanica)

Präferenzen beim Gebrauch von Konklusionsmarkern im Französischen und im Deutschen - Kunert, Irene Dorothea (Comparatio delectat IV (vorläufiger Titel; Artikel eingereicht 2023))

Nächtliche sympathische Aktivität und subjektive Symptome nach sport-assoziierter Concussion: eine Pilotstudie - Delling, Anne Carina; Jakobsmeyer, Rasmus; Christiansen, Nele; Coenen, Jessica; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Eine sport-assoziierte Concussion (saC) ist eine oftmals unterschätzte Hirnverletzung, die vor allem in Kontakt- und Kollisionssportarten häufig vorkommt. SaCs können zu einer Vielzahl an klinischen Symptomen führen. Akute und zum Teil die klinische Regeneration überdauernde parasympathische Inhibierung im Autonomen Nervensystem (ANS) wurde nach saC bereits häufig beschrieben. Über Veränderungen im sympathischen Nervensystem ist jedoch noch wenig bekannt. Diese wurden durch Messungen der elektrodermalen Aktivität (EDA) im Schlaf, der erheblich zur Regeneration nach saC beiträgt, sowie im Zusammenhang mit subjektiven Symptomen nach saC im Rahmen einer Pilotstudie untersucht. Methode 18 Sportler und Sportlerinnen mit diagnostizierter saC und 18 nach Alter, Geschlecht, Größe, Gewicht, Sportart und Leistungsklasse gematchte Kontrollathleten und -athletinnen trugen in den Nächten während der individuellen Return-to-Sport (RTS) Phase sowie drei Wochen nach Abschluss des RTS (postRTS) einen Handgelenkssensor (E4 Empatica Inc., Mailand, Italien). Anteile nächtlicher tonischer (meanEDA) und phasischer (EDRs, Schlafstürme) EDA wurden zwecks Gruppenvergleich ermittelt und mit saC-Symptomen (SCAT5) sowie dem subjektiven Erholungszustand nach Schlaf mittels Mann-Whitney U-Tests oder ungepaarten t-Tests verglichen. Ergebnisse Während und nach dem RTS konnten keine Gruppenunterschiede in den nächtlichen EDA-Parametern nachgewiesen werden. Eine höhere meanEDA während des RTS korrelierte mit einer höheren Anzahl an Symptomen (p=0,025, r=0,525) und eine erhöhte phasische EDA mit einem geringeren Anstieg des subjektiven Erholungszustands von vor zu nach Schlaf (EDRs: p=0,007, r=−0,642; EDRs/min: p>0,001, r=−0,762; Schlafstürme: p=0,011, r=−0,616). Fazit Die nächtliche EDA nach saC unterschied sich während und nach dem RTS nicht signifikant zu gematchten Kontrollsportlern und -sportlerinnen. Der Zusammenhang zwischen höherer EDA während des RTS und der Anzahl an saC-Symptomen sowie der geringeren subjektiven Erholung nach Schlaf könnte sowohl ursächlich für als auch Effekt der subjektiven Symptome sein und sollte durch Baseline-Messungen und in Kombination mit parasympathischen Markern künftig weiter untersucht werden.
Keywords: General Medicine

Large Scale Scanning of TLS Session Ticket Confusion - Storm, Tim Leonhard
Session tickets are a resumption mechanism, which can speed up repeated TLS connections. To do so, information is stored client-side, encrypted with an additional symmetric key, which is separate from existing private keys. A server only has to store this key, making session tickets stateless for the server. If the key is shared between servers, a client can be misled into resuming a session with a different, less secure server. In this thesis, we design and implement a scan for detecting prerequisites to such an attack, by requesting and redeeming tickets for pair-wise servers. We find that 17,901 out of 22,127 scanned (virtual) hosts are potentially vulnerable to this attack because they share their keys and accept tickets issued for other domains. We discuss the difficulties of detecting such an attack and show that unfortunately, our approach does not scale to larger sample sizes.

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Communications in Computer and Information Science)

Rezension zu: Bette, K.-H. & Kühnle, F.: Flitzer im Sport – Zur Sozialfigur des Störenfrieds - Sennefelder, Lisa (Sport und Gesellschaft)

Self-Stabilizing Skip-Graph with Growth-bounded Metric - Beckendorf, Björn

khiṭāb al-karāhiya – iṭlāla ʿala taʾwīlāt maghlūṭa li-n-nuṣūṣ al-islāmiya (Hassrede – Überblick auf kritische Interpretationen islamischer Texte) - Abdelrahem, Mohammed (khiṭāb al-karāhiya wa-taḥaddiyāt al-ḥiwār – taqāṭuʿāt wa-muwāǧahāt (Hassrede und die Herausforderungen des Dialogs – Überschneidungen und Konfrontationen))
Keywords: Dialog der Religionen; interreligiöser Dialog; Hass; Hassrede

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (ESANN 2023 proceedings)

SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (NeurIPS 2023 - Advances in Neural Information Processing Systems)

LitCQD: Multi-Hop Reasoning in Incomplete Knowledge Graphs with Numeric Literals - Demir, Caglar; Wiebesiek, Michel; Lu, Renzhong; Ngonga Ngomo, Axel-Cyrille; Heindorf, Stefan (ECML PKDD)

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Inorganic Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐RuII complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Analytical Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (International Conference on Industry Sciences and Computer Science Innovation)

Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Towards a Data-Driven Product Management – Concepts, Advantages, and Future Research - Fichtler, Timm; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Megatrends, such as digitization or sustainability, are confronting the product management of manufacturing companies with a variety of challenges regarding the design of future products, but also the management of the actual products. To successfully position their products in the market, product managers need to gather and analyze comprehensive information about customers, developments in the products’ environment, product usage, and more. The digitization of all aspects of life is making data on these topics increasingly available – via social media, documents, or the internet of things from the products themselves. The systematic collection and analysis of these data enable the exploitation of new potentials for the adaption of existing products and the creation of the products of tomorrow. However, there are still no insights into the main concepts and cause-effect relationships in exploiting data-driven approaches for product management. Therefore, this paper aims to identify the main concepts and advantages of data-driven product management. To answer the corresponding research questions a comprehensive systematic literature review is conducted. From its results, a detailed description of the main concepts of data-driven product management is derived. Furthermore, a taxonomy for the advantages of data-driven product management is presented. The main concepts and the taxonomy allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.
Keywords: Product Lifecyle Management (PLM); Data Analytics; Data-driven Design; Engineering Management; Lifecycle Data

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

CFD-Untersuchungen der Fluiddynamik und des Wärmetransports an rauen Oberflächen - Hollenhorst, Viola; Kenig, Eugeny Y.

Modellierung der Reaktivabsorption in regellosen Schüttungen und modellbasierte Optimierung von Füllkörpern mit dem Ansatz der hydrodynamischen Analogien - Salten, Alexander Heinrich Johannes
Füllkörper spielen in industriellen Trennprozessen eine wichtige Rolle bspw. bei der Reinigung industrieller Abgase durch Absorption. Die Trennleistung von Füllkörperkolonnen wird üblicherweise mittels vereinfachter Stufenmodelle ermittelt, deren Modellparameter experimentell bestimmt werden müssen. Dies stellt eine große Schwäche von Stufenmodellen dar, da diese Parameterim Allgemeinen nicht auf verschiedene Stoffsysteme und Füllkörpertypen übertragbar sind.In dieser Arbeit wird ein Modell, basierend auf dem hydrodynamischen Analogieansatz, zur Beschreibung von Absorptionsvorgängen in Füllkörperkolonnen vorgestellt. Dabei ist die Geometrie der festen Phase direkt abhängig von der Füllkörpergeometrie und der Stochastik der Schüttung. Die tatsächlichen Strömungsverhältnisse in Füllkörperkolonnen werden erfasst und durch eine Kombination vereinfachter charakteristischer Strömungsformen reproduziert. Dies erlaubt die Verwendung rigoroser Transportgleichung. Dadurch enthält das Modell weniger experimentell zu ermittelnde Parameter und ist damit unabhängiger von Experimenten als vereinfachte Stufenmodelle. Das Modell wurde gegen experimentelle Daten zur CO2-Absorption in wässrige Natronlauge validiert. Mit dem entwickelten Modell wurde anschließend eine Parameterstudie durchgeführt, die der Unterstützung der Entwicklung neuer Füllkörpergeometrien dient. Dazu wurde eine Simulationsstudie durchgeführt, die den Einfluss der Füllkörpergeometrie auf die Trennleistung untersucht.

Einseitiges Widerstandselementschweißen für die stahlintensive Mischbauweise - Haak, Viktor; Meschut, Gerson; Epperlein, Maike; Schiebahn, Alexander; Reisgen, Uwe (25. DVS-Sondertagung Widerstandsschweißen)

Optimal scheduling of a large-scale power-to-ammonia process: Effects of parameter optimization on the indirect demand response potential - Hochhaus, Thorben; Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

Demand Side Management Implementation in Downstream Digestate Treatment of a Biomethane Biorefinery - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Chemical Engineering Transactions)

Decision support tool to determine the suitability of demand side management implementation in continuously operated processes – A biorefinery case study - Röder, Lilli; Etzold, Hendrik; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract The time‐dependent adjustment of a system's power demand simultaneously with current power generation is commonly referred to as demand side management (DSM). DSM strategies are based on the flexibility to purchase electricity at times when prices are low, which can result in monetary benefits. One option to increase the flexibility of continuously operated processes is to oversize them. From an economic point of view, this leads to an increased investment. DSM only serves an economic purpose if the monetary benefits exceed this increase in capital costs. The main goal of this contribution is to develop a decision support tool to help evaluate unit operations regarding their feasibility for DSM implementation. In a case study, the decision support tool was applied to show its functionality on a biomethane production plant. The results show that with the help of the decision support tool, evaluating unit operations concerning their economic DSM potential is possible.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

Intersektionalität und erzählte Welten – Einführung - Abrego, Verónica; Henke, Ina; Kißling, Magdalena; Lammer, Christina; Leuker, Maria-Th. (Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien)

Het verschil tussen strips en graphic novels (in Vlaanderen) - Lammer, Christina

Power-to-hydrogen and hydrogen-to-X energy systems for the industry of the future in Europe - Genovese, Matteo; Schlüter, Alexander; Scionti, Eugenio; Piraino, Francesco; Corigliano, Orlando; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)
Keywords: Hydrogen economy; Green hydrogen; Power-to-X; Hydrogen-to-X; Sector coupling

Pre-equilibrium photons from the early stages of heavy-ion collisions - Oscar Garcia-Montero, Oscar Garcia-Montero; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (arXiv:2308.09747)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity $η/s$ and entropy density $dS/dζ \sim {\scriptstyle \left(Tτ^{1/3}\right)^{3/2}}_∞$. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in $\sqrt{s_{NN}}=2.76\,\text{TeV}$ 0-20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.

Open Educational Resources in der beruflichen Bildungslandschaft - Schneider, Jennifer Nicole

Experimental Study of an Internally Channeled Tube Heat Exchanger under Turbulent Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

Numerical analysis of failure modeling in clinching process chain simulation - Bielak, Christian Roman; Böhnke, Max; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. The application of the mechanical joining process clinching allows the assembly of different sheet metal materials with a wide range of material thickness configurations, which is of interest for lightweight multi-material structures. In order to be able to predict the clinched joint properties as a function of the individual manufacturing steps, current studies focus on numerical modeling of the entire clinching process chain. It is essential to be able to take into account the influence of the joining process-induced damage on the load-bearing capacity of the joint during the loading phase. This study presents a numerical damage accumulation in the clinching process based on an implemented Hosford-Coulomb failure model using a 3D clinching process model applied on the aluminum alloy EN AW-6014 in temper T4. A correspondence of the experimentally determined failure location with the element of the highest numerically determined damage accumulation is shown. Moreover, the experimentally determined failure behavior is predicted to be in agreement in the numerical loading simulation with transferred pre-damage from the process simulation.

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

Experimental and Numerical Investigation of Clinched Joints Under Shear Tensile Loading at High Strain Rates - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Karneval und OWL - Breckner, Anne

Auszeit - Breckner, Anne

Was brauchst du? Engagement für die Mitmenschen in Christentum und Islam. Interreligiöse Unterrichtsreihe im Themenheft Diakonie - Breckner, Anne; Kamcili-Yildiz, Naciye (Religion 5-10)

Economic Integration of a High-Temperature Heat Pump with Flexible Part-load Operation - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Untersuchung des Reibungs- und Deformationsverhaltens von schnelllaufenden Bremsen - Rauhaus, Johann; Schadomsky, Magnus; Magyar, Balázs; Zimmer, Detmar (Tagungsband der 64. Tribologie-Fachtagung)

Determination and Compensation of the Shrinkage Behavior of Cylindrical Elements in the FDM Process - Koers, Thorsten; Magyar, Balázs (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
Fused Deposition Modeling (FDM) is an additive manufacturing process to produce complex thermoplastic geometries layer by layer. The filament is melted in a nozzle, iteratively deposited, and then cools down. Due to the solidification process, the deposited filament strands deviate from their intended position due to shrinkage, resulting in significant geometric deviations in the final part. In terms of dimensional accuracy, there is a need for optimization, especially for local curved geometries in relation to the global part with higher nominal dimensions. The aim of this study is to investigate the size and shape deviations for cylindrical FDM elements and to compensate the expected deformations by using an in-house software with adaptive scaling factors in the x-y plane. Previous studies mainly focus on simple, non-curved objects, this study also considers the influence of curvature and global as well as local deviations on the final part.

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depictio is editable and extendable.

Übergang Schule-Beruf als Chancenverbesserungssystem – Zur Gestaltung von Lebensräumen und Entwicklung von Praktiken für den Übergang - Kremer, H.-Hugo; Otto, Franziska (bwp@ Berufs- und Wirtschaftspädagogik – online)
Sich wandelnde Bedingungen auf dem Ausbildungsmarkt, die daraus resultierenden veränderten Kompetenz- und Qualifikationsanforderungen sowie Anforderungen an eine lebensbegleitende berufliche Orientierung treffen insb. als (ausbildungs-)benachteiligt gekennzeichnete Jugendliche am Übergang Schule-Beruf. Jene Jugendliche münden in Maßnahmen des Übergangssystems wie die Ausbildungsvorbereitung (AV), wobei die konkreten Auswirkungen dieser Transformationsprozesse für diese Zielgruppe weitgehend unklar bleiben. In unserem Beitrag greifen wir die Überlegungen der Arbeitsgruppe 9+1 zum Übergangssystem verstanden als Chancenverbesserungssystem auf und diskutieren, was hierunter verstanden werden kann. Schließlich führen wir konkrete Anforderungen an das Chancenverbesserungssystem mit den Handlungsmöglichkeiten der Jugendlichen zusammen. Grundlegend verfolgen wir dabei nicht die Perspektive einer Anpassung der Jugendlichen an die Arbeitswelt, sondern fragen vielmehr danach, was Bildung leisten muss. Hierfür nehmen wir über qualitative Fallstudien die Perspektive der Jugendlichen sowie die Sichtweise des Bildungspersonals auf. In diesem Rahmen führen wir eine anforderungs- und subjektorientierte Perspektive zusammen und diskutieren u. a. anhand von Perspektiven auf das System, die curriculare Ebene, die Haltung der Bildungsakteur*innen, etc., was mit einer Gestaltung des Übergangssystems als Chancenverbesserungssystem konkret verbunden wäre.
Keywords: Übergangssystem; Selbstinszenierung; Chancenverbesserung; Subjektorientierung; Übergang Schule-Ausbildung

Modeling Highlighting of Metaphors in Multitask Contrastive Learning Paradigms - Sengupta, Meghdut; Alshomary, Milad; Scharlau, Ingrid; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: EMNLP 2023)